DIAGNOSTIC TEST OF NEUTROPHIL LYMPHOCYTE RATIO IN CONFIRMED COVID-19 POSITIVE PATIENT AT RSUD WONOSARI - Muhammad Ariq Naufal Arofiq; Linda Rosita; Utami Mulyaningrum (Universitas Muhammadiyah Surakarta, 2026)
Coronavirus Disease 2019 (Covid-19) is an outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The neutrophil lymphocyte ratio (NLR) biomarker is used as a parameter of inflammatory reactions which is also frequently evaluated in Covid-19. In Covid-19 patients, there is often an increase in NLR through the mechanism of lymphocyte exhaustion. This research to identify the performance of NLR in a diagnostic test for confirmed Covid-19 patients at RSUD Wonosari. This study is analytical observational through a cross-sectional approach. Sampling used a consecutive sampling technique. The target population was suspected Covid-19 patients. Data were analyzed by univariate, ROC curve, and diagnostic tests. A total of 75 suspected Covid-19 patients were found 33 male patients (44%), 42 female patients (66%), and the most aged> 55 years were 52 patients (69.3%). RT-PCR results found 57 patients were positive for Covid-19 (76%) and 18 patients were negative for Covid-19 (24%). ROC curve obtained AUC value 0.785 (p<0.05; 95% CI 0.662-0.907) with cut-off point NLR≥ 2.33, sensitivity 91.2%, specificity 50%, NPV 64.3%, PPV 85.2%, LR+ 1.81, and LR- 0.17. NLR can be an initial diagnostic tool for Covid-19.